2012
DOI: 10.1161/circresaha.112.270520
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Exaggerates Adventitial Inflammation and Angiotensin II−Induced Abdominal Aortic Aneurysm in Mice

Abstract: A bdominal aortic aneurysm (AAA), characterized by chronic aortic wall inflammation and destructive connective tissue remodeling, is one of the leading causes of sudden death in aging men (>55 years).1 Despite the current progress of surgical invasive repair or medical treatment, we lack a strategy to predict AAA rupture or to delay its progression. Epidemiological studies have identified several risk factors associated with AAA, including aging, male sex, smoking, and hypertension.1-3 However, the cause of AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 46 publications
9
131
0
1
Order By: Relevance
“…The pathogenesis of AAA is possibly initiated by macrophage recruitment into the adventitia, then presentation in the media. 22 Various proinflammatory cytokines are secreted from the vessel cells to induce more inflammatory cells. 38 In the 2 AAA models, IMD successfully suppressed the protein expression of proinflammatory cytokines IL-6 and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathogenesis of AAA is possibly initiated by macrophage recruitment into the adventitia, then presentation in the media. 22 Various proinflammatory cytokines are secreted from the vessel cells to induce more inflammatory cells. 38 In the 2 AAA models, IMD successfully suppressed the protein expression of proinflammatory cytokines IL-6 and MCP-1.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, we found similar effects of IMD on the mRNA expression of IL-6, MCP-1, and interferon-γ in aortic walls. Aortic adventitial fibroblasts may be involved in vascular wall inflammation and remodeling in AAA by transforming into α-actin-positive myofibroblasts and producing proinflammatory cytokines, 22 which, at least in part, was modulated by oxidative stress. 8,26 We found that IMD and antioxidant NAC both decreased the protein expression of IL-6, MCP-1, nuclear factor-κB, and tumor necrosis factor-α in adventitial fibroblasts, where proinflammatory cytokines are mainly observed in AAA according to our present and previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have suggested the existence of an interaction between Hcy and angiotensin II (ANG II) signaling as a pathway that contributes significantly to the potential oxidative stress in the vasculature (2,31). Some studies have addressed the possibility of ANG II signaling-related proteins, such as angiotensinconverting enzyme (ACE), serving as a target of Hcy (4,30,34). However, these studies reported general correlations between HHcy and ANG II/ACE signaling in different disease models.…”
mentioning
confidence: 99%